An unbiased seed-based RNAi selection screen identifies small RNAs that inhibit androgen signaling and prostate cancer cell growth - Joshua M. Corbin; Constantin Georgescu; Lin Wang; Jonathan D. Wren; Magdalena Bieniasz; Chao Xu; Adam S. Asch; Maria J. Ruiz Echevarría (Elsevier, 2023)
Blocking androgen receptor signaling is the mainstay of therapy for advanced prostate cancer (PCa). However, acquired resistance to single agents targeting this pathway results in the development of lethal castration-resistant PCa. Combination therapy approaches represent a promising strategy for the treatment of advanced disease. Here, we explore a therapeutic strategy for PCa based on the ability of shRNAs/siRNAs to function essentially as miRNAs and, via seed sequence complementarity, induce RNA interference of numerous targets simultaneously. We developed a library that contained shRNAs with all possible seed sequence combinations to identify those ones that most potently reduce cell growth and viability when expressed in PCa cells. Validation of some of these RNAi sequences indicated that the toxic effect is associated with seed sequence complementarity to the 3' UTR of AR coregulatory and essential genes. In fact, expression of siRNAs containing the identified toxic seed sequences led to global inhibition of AR-mediated gene expression and reduced expression of cell-cycle genes. When tested in mice, the toxic shRNAs also inhibited castration-resistant PCa and exhibited therapeutic efficacy in pre-established tumors. Our findings highlight RNAi of androgen signaling networks as a promising therapeutic strategy for PCa.